Hegel and the Spiritual Evolution of Absolute Subject - Minkov, Ivo (ETHICS IN PROGRESS, 2021)
The article interprets the methodological potential of Hegel’s speculative dialectics as a possible course of spiritual evolution of the Absolute subject. The intention is towards the method, first through the very construction of the “idea of freedom” from the point of view of Logic; second, through the constitutive function of freedom and the transition of the subjective spirit into the objective spirit; third, through the unfolding of mediation in the realms of the objective spirit. This essentially substantial methodologization dissolves the theoretical space of the idea of the mediating function of freedom as an ontological principle of ethical life. In line with the paradigm of such a course, the text considers a project of speculative ethics, a project within the framework of which the methodological and ontological sublation of spiritual evolution takes place.